2012
DOI: 10.4172/2157-7609.1000134
|View full text |Cite
|
Sign up to set email alerts
|

Acetamiprid Induces Toxicity in Mice under Experimental Conditions with Prominent Effect on the Hematobiochemical Parameters

Abstract: The present study was carried out to assess the toxicological effect of acetamiprid, an insecticide of neonicotinoid group on clinical and serum hematobiochemical parameters of mice. The experimental animals were divided into four different groups of equal number of animals and the first group was considered as Control. It was found that acetamiprid administered @ 40 mg/kg body weight per day (1/5 th of LD% value) for a period of 28 days induces prominent toxic symptoms along with hematological and biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 4 publications
3
17
0
Order By: Relevance
“…In fact, the administration of ACT at a dose of 20 mg/kg BW/day for 21 consecutive days caused a significant decrease in red blood cells (RBC) count, hemoglobin (Hb) content and hematocrit (HCT) level which indicates the installation of hemolytic anemia compared to the control group ( Table ). These results were in accordance with previous works …”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…In fact, the administration of ACT at a dose of 20 mg/kg BW/day for 21 consecutive days caused a significant decrease in red blood cells (RBC) count, hemoglobin (Hb) content and hematocrit (HCT) level which indicates the installation of hemolytic anemia compared to the control group ( Table ). These results were in accordance with previous works …”
Section: Resultssupporting
confidence: 94%
“…ACT treated mice showed normocytic normochromic anemia as their MCV (mean corpuscular volume), MCH (mean corpuscular hemoglobin content) and MCHC (mean corpuscular concentration in hemoglobin) values did not significantly differ from controls ( Table ). Our findings were similar to previous researches using different types of xenobiotics, and were reinforced by many reports concerning acetamiprid exposure …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding were in agreement withmany authorsVohra and Khera, (37) who showedimidacloprid, neonicotinoid, caused reduction in platelet count and disturbed blood clotting.Gawadeet al, (38) reported that imidacloprid reduced in Hb content may be due to increased rate of breakdown of red cells and/or reduction in the rate of formation of RBC's (39) . Furthermore, Singh et al, (40) who suggested that acetamiprid in mice decreased Hb levels. Our finding agreement with Roy and Nath, (41) who showed that THIA caused reduction in RBCs count and Hb level due to the destruction of RBCtriggered by the arrival of THIA into erythrocytes, and WBCs increase during higher doses of THIA attributed to the production of a greater amount of antibodies (42) .…”
Section: Histological Studies In All Studied Groupsmentioning
confidence: 99%